2015
DOI: 10.1038/srep07771
|View full text |Cite
|
Sign up to set email alerts
|

Co-immunization with DNA and protein mixture: A safe and efficacious immunotherapeutic strategy for Alzheimer's disease in PDAPP mice

Abstract: Active immunotherapy targeting β-amyloid (Aβ) is the most promising strategy to prevent or treat Alzheimer's disease (AD). Based on pre-clinical studies and clinical trials, a safe and effective AD vaccine requires a delicate balance between providing therapeutically adequate anti-Aβ antibodies and eliminating or suppressing unwanted adverse T cell-mediated inflammatory reactions. We describe here the immunological characterization and protective efficacy of co-immunization with a 6Aβ15-T DNA and protein mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…ACI-24 also improved novel object recognition without triggering proinflammatory responses [73]. Finally, DNA vaccines against Aβ1-42 [98,99], alone or in combination with protein antigens [100,101], have shown promising results at the preclinical stage. DNA-based vaccination utilizes direct injection of DNA-encoding genes for protein or peptide antigens, and it does not require the use of adjuvants.…”
Section: Immunotherapy Targeting Aβmentioning
confidence: 99%
See 1 more Smart Citation
“…ACI-24 also improved novel object recognition without triggering proinflammatory responses [73]. Finally, DNA vaccines against Aβ1-42 [98,99], alone or in combination with protein antigens [100,101], have shown promising results at the preclinical stage. DNA-based vaccination utilizes direct injection of DNA-encoding genes for protein or peptide antigens, and it does not require the use of adjuvants.…”
Section: Immunotherapy Targeting Aβmentioning
confidence: 99%
“…DNA-based vaccination utilizes direct injection of DNA-encoding genes for protein or peptide antigens, and it does not require the use of adjuvants. Coimmunization with a mixture of Aβ1-42 DNA and protein is capable of inducing Th2-type Aβ-specific antibodies while simultaneously suppressing unwanted inflammatory reactions and avoiding T-cell-mediated autoimmune responses [100].…”
Section: Immunotherapy Targeting Aβmentioning
confidence: 99%
“…Whether this particular method of immunization is protective in transgenic AD-models remains to be determined, however the induction of a non-inflammatory, Th2/Treg type response was encouraging. Indeed Liu and colleagues have demonstrated that coimmunization with Aβ 1-15 DNA and Aβ 1-15 peptide induced Aβ-specific Th2 responses, resulting in improved spatial memory and reduced plaque deposition in PDAPP mice (Liu et al 2015). Together these results suggest that an antiinflammatory immunotherapy may be a more sensible treatment for this disease.…”
Section: Protective Role For T Cells In Ad; Immunizationmentioning
confidence: 93%
“…The Th2-biased response induced by the immunogen expressed in DNA vaccinated mice yielded anti-Aβ antibodies, which reduced the brain's burden for that protein without inflammation. This immunoresponse was increased by either priming with the peptide immunogen followed by genetic vaccination (Lambracht-Washington and Rosenberg, 2012), or by co-immunization with DNA and Aβ mixtures (Liu et al, 2015). Of relevance for AD protection is that in different animal species, DNA vaccination induces antibodies directed to linear Aβ, as well as its relevant conformational epitopes and toxic oligomers (Matsumoto et al, 2013).…”
Section: Dna Vaccines or Genetic Immunizationmentioning
confidence: 98%